Behavior of the Surviving Population of Listeria monocytogenes and Salmonella Typhimurium Biofilms Following a Direct Helium-Based Cold Atmospheric Plasma Treatment - Govaert, Marlies; Smet, Cindy; Acquah, Cyril; Walsh, James L.; Van Impe, Jan F. M. (Frontiers in Microbiology, 2022)
Although the Cold Atmospheric Plasma (CAP) technology proved promising for inactivation of biofilms present on abiotic food contact surfaces, more research is required to examine the behavior of the CAP surviving biofilm-associated cells. It was therefore examined whether (i) CAP treated (L. monocytogenes and S. Typhimurium) biofilm-associated cells were able to further colonize the already established biofilms during a subsequent incubation period and (ii) isolates of the surviving population became less susceptible towards CAP when the number of biofilm development - CAP treatment cycles increased. For this purpose, a direct treatment was applied using a helium-based Dielectric Barrier Discharge electrode configuration. Results indicated that the surviving population was able to further colonize the already established biofilms, since the cell density of the CAP treated + incubated biofilms equaled the initial density of the untreated biofilms. For the L. monocytogenes biofilms, also the total biomass proved to further increase, which might result in an even further increased resistance. The susceptibility of the biofilm-associated cells proved to be influenced by the specific number of CAP treatment cycles, which might potentially result in an overestimation of the CAP treatment efficacy and, consequently, an increased risk of food contamination.